The factors influencing knowledge entrepreneurship in Malaysian manufacturing companies. - Jusoh, Rosnani; Asimiran, Soaib; Ziyae, Babak (2010)
Established firms that continuously and systematically implement entrepreneurial initiatives exhibit behavior that corporate entrepreneurship researchers label as “sustained regeneration”. A prime example of sustained regeneration is new product development activity in industries such as computers, electronics, and textiles where the introduction of new products is on-going and firm’s creativities have important implications to its performance. On the other hand, knowledge entrepreneurship describes the organizational ability to respond to learn to capitalize on an opportunity, or to protect against a threat by adopting an innovation. Successful adoption of innovation requires an organizational ability to manage the process within the organization that deals with new or newly interpreted knowledge and under conditions of uncertainty and in the face of controversy, develop and initiate a plan of action to respond with goal-oriented organizational behavioral changes. Knowledge entrepreneurship connotes a “drive to implement change, to accomplish this goal, and to adopt an innovation”. Knowledge entrepreneurship involves a motivated pursuit of competitive advantage, using knowledge as a means of developing sources of advantage similar to those described in the market orientation and absorptive capacity literatures. It describes a driven effort to utilize knowledge through innovation. This article is identifying knowledge entrepreneurship, and determining which factors may affect the nature of this concept. The selected criteria have been assessed according to their relative importance by utilizing analytical hierarchy process (AHP) approach and expert choice software program.